A new species of the Genus Hebius Thompson, 1913 (Squamata: Colubridae) from Baise, Guangxi, China - Xu, Yu-Hao; Yang, Dian-Cheng; Gong, Yan-An; Wu, Jia-Xiang; Huang, Ru-Yi; Liu, Yong-Jin; Liang, Sheng-Ming; Huang, Tian-Qi; Huang, Song (Zootaxa, 2023)
A new species of the genus Hebius Thompson, 1913 is described from Youjiang District, Baise City, Guangxi Zhuang Autonomous Region, China, based on a single adult female specimen. It can be distinguished from its congeners by the following combination of characters: (1) dorsal scale rows 19-17-17, feebly keeled except the outermost row; (2) tail length comparatively long, TAL/TL ratio 0.30 in females; (3) ventrals 160 (+ 3 preventrals); (4) subcaudals 112; (5) supralabials 9, the fourth to sixth in contact with the eye; (6) infralabials 10, the first 5 touching the first pair of chin shields; (7) preocular 1; (8) postoculars 2; (9) temporals 4, arranged in three rows (1+1+2); (10) maxillary teeth 30, the last 3 enlarged, without diastem; (11) postocular streak presence; (12) background color of dorsal brownish black, a conspicuous, uniform, continuous beige stripe extending from behind the eye to the end of the tail; (13) anterior venter creamish-yellow, gradually fades to the rear, with irregular black blotches in the middle and outer quarter of ventrals, the posterior part almost completely black. The discovery of the new species increases the number of species in the genus Hebius to 51.